Strategi Komunikasi Dalam Pembentukan Organisasi Komite Sekolah di TK Negeri Sendang Kabupaten Cirebon - Dwi Janur Wulan; Sofyan Mustoip; Novi Hidayati (Sekolah Tinggi Agama Buddha Nalanda, 2023)
The government is trying to achieve the goals of National Education in accordance with Law No. 20 of 2003, which is to develop the potential of students to become human beings of faith and piety. Education is defined as a conscious and planned effort to create a learning atmosphere in order to develop students' self-potential. The responsibility for education is left to parents, educational institutions, government, and society. Research at TKN Sendang, Cirebon District, used a qualitative method to analyze the formation and role of the School Committee in early childhood education. The results showed that the School Committee at TKN Sendang played a role in improving the quality of education by providing direction, staff support, facilities, and supervision at the early age level. The active role of parents/guardians of students is very significant in supporting and involving themselves in School Committee activities, including providing input and financial support. The School Committee is also effective in providing direction and support for character building and improving learning facilities. In conclusion, the active participation of parents/guardians of students and the role of the School Committee is important in improving the quality of early childhood education. Collaboration between the government, educational institutions, the community, and parents/guardians of students creates an educational environment that is conducive and supports the optimal growth of the potential of students, so as to achieve the goals of National Education that have been set.